2021
DOI: 10.1038/s41467-021-26061-w
|View full text |Cite
|
Sign up to set email alerts
|

Ring finger protein 213 assembles into a sensor for ISGylated proteins with antimicrobial activity

Abstract: ISG15 is an interferon-stimulated, ubiquitin-like protein that can conjugate to substrate proteins (ISGylation) to counteract microbial infection, but the underlying mechanisms remain elusive. Here, we use a virus-like particle trapping technology to identify ISG15-binding proteins and discover Ring Finger Protein 213 (RNF213) as an ISG15 interactor and cellular sensor of ISGylated proteins. RNF213 is a poorly characterized, interferon-induced megaprotein that is frequently mutated in Moyamoya disease, a rare … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 111 publications
(114 reference statements)
5
80
0
Order By: Relevance
“…RNF213 is expressed at baseline levels in many tissues (Liu et al, 2011), but is upregulated by LPS, TNFa and interferon (IFN), supporting the idea that inflammatory and innate immune signals might act as potential environmental triggers for MMD (Kobayashi et al, 2015;Ohkubo et al, 2015;Bosch et al, 2020;Sarkar and Thirumurugan, 2020). RNF213 is present in the cytosol (Liu et al, 2011), but overexpression, oleic acid treatment (Sugihara et al, 2019), interferon or LPS stimulation (Bosch et al, 2020;Thery et al, 2021) target the protein to the surface of lipid droplets (LDs), organelles that regulate lipid storage but also act as intracellular innate immune hubs (Bosch et al, 2020). Overexpression of RNF213 stabilizes LDs, removing adipose triglyceride lipase (ATGL) from their surface and functioning as a positive regulator of fat storage in the cells (Sugihara et al, 2019).…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…RNF213 is expressed at baseline levels in many tissues (Liu et al, 2011), but is upregulated by LPS, TNFa and interferon (IFN), supporting the idea that inflammatory and innate immune signals might act as potential environmental triggers for MMD (Kobayashi et al, 2015;Ohkubo et al, 2015;Bosch et al, 2020;Sarkar and Thirumurugan, 2020). RNF213 is present in the cytosol (Liu et al, 2011), but overexpression, oleic acid treatment (Sugihara et al, 2019), interferon or LPS stimulation (Bosch et al, 2020;Thery et al, 2021) target the protein to the surface of lipid droplets (LDs), organelles that regulate lipid storage but also act as intracellular innate immune hubs (Bosch et al, 2020). Overexpression of RNF213 stabilizes LDs, removing adipose triglyceride lipase (ATGL) from their surface and functioning as a positive regulator of fat storage in the cells (Sugihara et al, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…Most interestingly, we demonstrated that RNF213, through its binding to ISG15, has a broad antimicrobial activity in vitro and in vivo, counteracting infection against Listeria monocytogenes, human respiratory syncytial virus (RSV), coxsackievirus (CV) B3 and herpes simplex virus 1 (HSV-1). Along with a striking co-localization of RNF213 with intracellular bacteria, these findings uncovered a new role of RNF213 as a key antimicrobial effector (Thery et al, 2021). Similarly, it was recently shown that RNF213 counteracts Salmonella through the ubiquitylation of LPS, independent of its naming RING domain, but instead relying on an RZ finger in the E3 shell (Otten et al, 2021).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations